Multiple evolutionary lineages for the main vector of Leishmania guyanensis, Lutzomyia umbratilis (Diptera: Psychodidae), in the Brazilian Amazon - Scarpassa, Vera Margarete; Cunha-Machado, Antônio Saulo; Alencar, Ronildo Baiatone (Scientific Reports, 2021)
Lutzomyia umbratilis is the main vector of Leishmania guyanensis in the Brazilian Amazon and in neighboring countries. Previous biological and molecular investigations have revealed significant differences between L. umbratilis populations from the central Brazilian Amazon region. Here, a phylogeographic survey of L. umbratilis populations collected from nine localities in the Brazilian Amazon was conducted using two mitochondrial genes. Statistical analyses focused on population genetics, phylogenetic relationships and species delimitations. COI genetic diversity was very high, whereas Cytb diversity was moderate. COI genealogical haplotypes, population structure and phylogenetic analyses identified a deep genetic differentiation and three main genetic groups. Cytb showed a shallower genetic structure, two main haplogroups and poorly resolved phylogenetic trees. These findings, allied to absence of isolation by distance, support the hypothesis that the Amazon and Negro Rivers and interfluves are the main evolutionary forces driving L. umbratilis diversification. The main three genetic groups observed represent three evolutionary lineages, possibly species. The first lineage occurs north of the Amazon River and east of Negro River, where Le. guyanensis transmission is intense, implying that L. umbratilis is an important vector there. The second lineage is in the interfluve between north of Amazon River and west of Negro River, an area reported to be free of Le. guyanensis transmission. The third lineage, first recorded in this study, is in the interfluve between south of Amazonas River and west of Madeira River, and its involvement in the transmission of this parasite remains to be elucidated. © 2021, The Author(s).